2016
DOI: 10.1007/s00167-016-4295-7
|View full text |Cite
|
Sign up to set email alerts
|

Area of the tibial insertion site of the anterior cruciate ligament as a predictor for graft size

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Finally, the third study reported good agreement between MRI and intraoperative measurement of the area of the ACL tibial insertion site. 5 These findings confirm that the size of the ACL tibial footprint on MRI could be a useful parameter for predicting its actual size.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Finally, the third study reported good agreement between MRI and intraoperative measurement of the area of the ACL tibial insertion site. 5 These findings confirm that the size of the ACL tibial footprint on MRI could be a useful parameter for predicting its actual size.…”
Section: Discussionsupporting
confidence: 77%
“…Several previous studies showed that the shape of the ACL tibial footprint differs among patients (elliptical, triangular, C-shape, etc). 5,6,26,27 Therefore, the size of the ACL tibial footprint also differs. 15,16,23,24,26 Predictive equations for actual size that were developed on the basis of MRI measurement and sex showed good concordance correlation coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison between our results and those of other authors, by the various modes of evaluation, is found in ►Table 3. [3][4][5][6][7][8][9][10][11][12][13][18][19][20][21][22][23][24] In fact, Lord et al 25 published a study of the function of the ACL tibial insertion fibers in the resistance of anterior and rotational displacements, with robotics, in six degrees of freedom of movement. They concluded that the central, posterior and lateral fibers of the ACL tibial insertion play a secondary role in the restriction of tibial displacements and that the most important fibers are the anterior and the anteromedial peripheral portion.…”
Section: Discussionmentioning
confidence: 99%
“…4 Therefore, anticipating the dimensions of the ACL insertion can be valuable for better surgical planning. This can be done by CT scan 5,6 or magnetic resonance imaging (MRI), [7][8][9][10][11] but it can also be predicted by the individual physical characteristics. 3,4 In this decade, some authors sought to correlate the weight and height of patients with the size of their tibial ACL insertion.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published papers have noted individual variations in patients' native ACL anatomy, such as in terms of the tibial insertion site, which may influence graft size. 25 , 26 Therefore patient-specific ACL reconstruction using individualised graft characteristics to reproduce native patient anatomy may pave the way to better functional and structural outcomes.…”
Section: Discussionmentioning
confidence: 99%